Relationship of zooplankton and environmental parameter with emphasis on copepods at Pulau Tinggi, Johor, Malaysia - Shuaib, Nasir (2021)
There is little information on the effect of environmental parameters on the zooplankton biomass and density in the marine ecosystem. This research added on to the knowledge as results proposes statistical modeling including aspects of biomass and density to environmental parameters. The objectives are (i) to determine the impacts of environmental changes on zooplankton density and biomass in the coastal water of Pulau Tinggi, Johor, (ii) To determine the community structure and biodiversity of copepods in the coastal water of Pulau Tinggi Johor, (iii) To apply multiple linear regression model on the relationship between the copepods and environmental parameters in the coastal water of Pulau Tinggi. The collected zooplankton samples were taken to the laboratory of UTHM and further analyzed for density and biomass of 3 size fractions. Environmental parameters were measured in situ. Biomass and density of zooplankton were dependent variables while environmental parameters were independent variables. Zooplankton was classified into seven taxonomic groups; copepods, larvaceans, chaetognaths, cnidarians, ctenophores, decapods and polychaetes. The copepods were categorized in to four orders; Calanoida, Poecilostomatoida, Cyclopoida and Harpacticoida. This included a total of 54 species, 26 genera and 19 families of copepods. Calanoida was the abundant group represented by 36 species in our study. The values of diversity index showed that Pulau Tinggi sea grass bed was considered the moderate diverse ecosystem during the research period. Results showed that statistical model of small size zooplankton (< 500 μm) is the best model for the zooplankton biomass. Water depth, turbidity, water current, temperature and salinity were significant variables for small size zooplankton model. This model could be used for the prediction and estimation of zooplankton biomass. The Principal component analysis (PCA) showed that environmental parameters like water current, rainfall, tide, nitrates and rainy days strongly influencing the biomass and density of copepod.